2019
DOI: 10.1210/en.2019-00398
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Glucagon-Like Peptide-2 Receptor Expression in the Mouse

Abstract: Glucagon-like peptide-2 (GLP-2), secreted from enteroendocrine cells, attenuates gut motility, enhances barrier function, and augments nutrient absorption, actions mediated by a single GLP-2 receptor (GLP-2R). Despite extensive analyses, the precise distribution and cellular localization of GLP-2R expression remains controversial, confounded by the lack of suitable GLP-2R antisera. Here, we reassessed murine Glp2r expression using regular and real-time quantitative PCR (qPCR), in situ hybridization (ISH), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 55 publications
4
30
0
Order By: Relevance
“…In line with this, GLP-2 acutely stimulates glucagon secretion (11). Consistent but low GLP-2R mRNA was confirmed in rodent acell lines as well as in a human b-cell line and in mouse islets (12), the latter being in contrast to a more recent study (13). GLP-2 had no effect on glucose-stimulated insulin secretion (GSIS) in isolated mouse islets (12).…”
Section: Introductionsupporting
confidence: 56%
“…In line with this, GLP-2 acutely stimulates glucagon secretion (11). Consistent but low GLP-2R mRNA was confirmed in rodent acell lines as well as in a human b-cell line and in mouse islets (12), the latter being in contrast to a more recent study (13). GLP-2 had no effect on glucose-stimulated insulin secretion (GSIS) in isolated mouse islets (12).…”
Section: Introductionsupporting
confidence: 56%
“…The GLP-2R is not expressed on enterocytes (El-Jamal et al, 2014;Pedersen et al, 2015) that are responsible for CM intracellular synthesis and assembly. Instead, it is mostly identified on enteric neurons, myofibroblasts, and stromal cells (Yusta et al, 2000(Yusta et al, , 2019Ørskov et al, 2005;Guan et al, 2006;Wismann et al, 2017), which are abundantly present in the subepithelial regions of the intestine, including the lamina propria. It has been suggested that GLP-2-induced intestinal wound repair may involve vascular endothelial growth factor (VEGF) secretion from fibroblasts (Bulut et al, 2008).…”
Section: Oral Glucose and Glp-2 As Stimuli Of Intestinal Lipid Mobilimentioning
confidence: 99%
“…1 Nonetheless, improved techniques suggest GLP-2R localization in subsets of subepithelial myofibroblasts, enteric neurons, and enteroendocrine cells from stomach to rectum. 5,6 Indeed, its expression in subepithelial myofibroblasts may represent the recently identified telocytes, which communicate with enteric neurons and the intestinal epithelium to mediate enterocyte proliferation, differentiation, migration, and repair in a paracrine manner. 7 In addition to GLP-2R expression, the proliferative effects of GLP-2 have been noted from duodenum to colon [8][9][10][11] ; therefore, its ability to amplify upper or lower gastrointestinal polyposis in patients with FAP cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%